Creative workflow in Lightroom : the photographer's guide to managing, developing, and sharing your work - Bradley, Jason (Photographer) (Focal Press, 2016)
Adobe's Lightroom has emerged as a must-have software due to its powerful editing tools and time saving organizational capabilities but how you establish a personalized, creative workflow that optimizes this technology, your time, and your art eludes most photographers. Jason Bradley, award-winning photographer and Lightroom pro, shares the answers to these questions in this practical and easy to follow guide that taps into the "how" and the "why" of a professional photographer's creative workflow in Lightroom. Bradley will show you how all workflows can be simplified into three steps: establishing, managing, and rendering the file, alongside stunning photographs and explanations from his own experiences. This book will not only teach you how to work within Lightroom but, ultimately, how to make Lightroom work for you